If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+4=2(3x-8)
We move all terms to the left:
2x+4-(2(3x-8))=0
We calculate terms in parentheses: -(2(3x-8)), so:We get rid of parentheses
2(3x-8)
We multiply parentheses
6x-16
Back to the equation:
-(6x-16)
2x-6x+16+4=0
We add all the numbers together, and all the variables
-4x+20=0
We move all terms containing x to the left, all other terms to the right
-4x=-20
x=-20/-4
x=+5
| 13=5+2w | | 18+4n=2(6-n) | | 3-3b=-7b+4b+3 | | 3(3x-3)=13 | | 2.1/2(2)=x | | 3x-100=-10x+30 | | 4(1/2x-1/4)=(2x+1/2) | | 4(1+4x)=52 | | 4x-9+2x+15=180 | | x+11+5x=8x-3 | | 3y-6=48 | | x2−4=−28 | | -3+24x+22x+7=180 | | 60/3+n/3=84/5+n/5 | | 2n=2.62 | | –8−7u=–6u | | (2^5)x+15=(4^5)x-6 | | 21/2(2)=x | | 6/7x+6=9 | | 16+2=-3(3x-6) | | 11x+1+16x+1=18x+11 | | -6*2+k=-20 | | -0.3z=-0.93 | | 3p=4p+7 | | 15a-10=-3(-5a+2) | | 3a+11=7a-13 | | -4=a/3-6 | | 1=4c+3 | | (5x+28)=(4x+31) | | 7e+3.3=6 | | -2(5-b)+2b=-6 | | 6x+2=4x–8 |